One on one : a Buddy Steel mystery - Brandman, Michael (Brandman, Michael. Buddy Steel mystery., 2018)
When legendary sheriff Burton Steel summons his son Buddy home from LAPD Homicide, a reluctant Buddy agrees. Burton is debilitated by ALS, Lou Gehrig's disease. While Buddy is to cover his back, not an assignment he wants, the clincher is it's his last chance to connect with his proud, overbearing parent. What Buddy doesn't expect is to encounter crime in Freedom, a privileged coastal community a hundred miles north of Los Angeles, as vicious and challenging as that of the city. One spring morning, the latest challenge erupts. The brutal murder of a prominent Freedom High School sports coach leads Buddy into a clandestine universe of sexual deception, play parties, unwitting athletes, over-privileged youths, treacherous bullies, and shocking malfeasance. At the same time, a sudden scourge of graffiti is disfiguring both public and private property, despoiling the beauty and serenity of Freedom's unassuming landscape. Outraged, knowing he has few legal weapons to wield, Buddy is forced to find new and challenging ways to thwart the street artist or artists responsible. Irreverent and imaginative, not to say manipulative, Buddy is just the man for the job.--Provided by Publisher.